Oligometastatic status as predictor of survival in metastatic human papillomavirus‐positive oropharyngeal carcinoma. Issue 8 (13th May 2018) - Albergotti, William G.; Abberbock, Shira; Mathews, Fasil; Ferris, Robert L.; Johnson, Jonas T.; Duvvuri, Umamaheswar; Kim, Seungwon
Abstract: Background: Oligometastasis is a good prognostic indicator when compared to widely metastatic disease in malignancies of other organ systems. We hypothesized that oligometastasis in human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (SCC) would be associated with better overall survival. Methods: This is a retrospective review of all HPV‐positive oropharyngeal SCC treated at one center with at least 1‐year of follow‐up. Patients were stratified into 2 cohorts: oligometastasis (1‐2 metastases, confined to 1 organ system) or polymetastasis (>2 metastases or multiple organ involvement) with cohorts compared for time to distant metastasis and overall survival after metastasis. Results: Thirty‐eight of 506 patients (7.5%) developed metachronous distant metastasis; 12 developed oligometastasis and 26 developed polymetastasis. Median overall survival after oligometastasis was significantly longer than polymetastasis at 45 months (95% confidence interval [CI] 19 months ‐ not reached) and 10 months (95% CI 5‐24 months; P = .00028). Conclusion: Oligometastasis in metastatic HPV‐positive oropharyngeal SCC portends a better prognosis than polymetastasis.